Unsaturated zwitter-ion-based polymer, unsaturated zwitter-ion-based polymer membrane, preparation method and application of unsaturated zwitter-ion-based polymer membrane and lithium ion battery

By using unsaturated zwitterion-based polymers as the electrolyte of lithium-ion batteries, the problems of insufficient conductivity and thermal stability of existing solid electrolytes are solved, and the high rate performance and cycling performance of lithium-ion batteries are achieved.

CN119798568AActive Publication Date: 2025-04-11浙江冠盛东驰能源科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510024555.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing solid-state polymer electrolytes have problems with low ionic conductivity and poor thermal stability, resulting in poor electrochemical performance of built solid-state lithium-ion batteries.

Method used

Unsaturated zwitterionic-based polymers are used as electrolytes, and a film material with high ionic conductivity, wide electrochemical window and excellent thermal stability is formed by combining polymerized monomers, crosslinking agents, unsaturated zwitterionic compounds, lithium salts, plasticizers and initiators.

Benefits of technology

The rate performance and cycle performance of lithium-ion batteries are improved, the thermal stability and electrochemical performance of the battery are enhanced, and the problems of insufficient conductivity and thermal stability of existing electrolytes are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798568A_ABST
    Figure CN119798568A_ABST
Patent Text Reader

Abstract

The invention provides an unsaturated zwitter-ion-based polymer, an unsaturated zwitter-ion-based polymer membrane, a preparation method and application of the unsaturated zwitter-ion-based polymer membrane, and a lithium ion battery. The unsaturated zwitterionic polymer provided by the invention is prepared from the following raw materials in parts by mass: 40 to 70 parts of polymeric monomer, 0.1 to 1 part of cross-linking agent, 1 to 10 parts of unsaturated zwitterionic compound, 20 to 30 parts of lithium salt, 5 to 20 parts of plasticizer and 0.1 to 1 part of initiator, the cross-linking agent contains an imino group and an unsaturated group. According to the invention, the unsaturated zwitterionic polymer has high ionic conductivity and wide electrochemical window, and has excellent thermal stability; when the lithium ion battery is assembled by using the solid electrolyte, the rate capability and the cycle performance of the obtained lithium ion battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and specifically relates to an unsaturated zwitterion-based polymer, an unsaturated zwitterion-based polymer film, a preparation method and application thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries (LIBs) are batteries with high energy density and long life. They have been widely studied and applied in energy storage devices such as portable electronic products and electric vehicles.

[0003] The electrolytes used in lithium-ion batteries are divided into two categories. One is the traditional liquid electrolyte. Although this liquid electrolyte is widely used, it has safety issues such as easy leakage, flammability and explosion, which hinder the mass production of lithium-ion batteries. The other is solid electrolyte. Solid electrolytes are not easy to leak, flammable and explosive, and have high safety. Solid-state lithium-ion batteries built based on solid electrolytes fundamentally solve the safety problems of traditional liquid lithium-ion batteries and have good application prospects.

[0004] Solid polymer electrolytes have high safety, flexibility, scalability and interface compatibility, making them promising solid electrolytes. The commonly used solid polymer electrolyte is polyethylene oxide (PEO). However, existing solid polymer electrolytes have the disadvantages of low ionic conductivity and poor thermal stability, and the electrochemical performance of solid-state lithium-ion batteries constructed from them is poor. Summary of the invention

[0005] The purpose of the present invention is to provide an unsaturated zwitterion-based polymer, an unsaturated zwitterion-based polymer film, a preparation method and application thereof, and a lithium-ion battery. The unsaturated zwitterion-based polymer provided by the present invention has high ionic conductivity and a wide electrochemical window, and has excellent thermal stability; when used as an electrolyte of a lithium-ion battery, it is beneficial to improve the rate performance and cycle performance of the lithium-ion battery.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides an unsaturated zwitterionic polymer, which comprises the following raw materials by weight:

[0008] 40-70 parts of polymerizable monomers, 0.1-1 parts of crosslinking agents, 1-10 parts of unsaturated zwitterionic compounds, 20-30 parts of lithium salts, 5-20 parts of plasticizers and 0.1-1 parts of initiators; the crosslinking agent contains imino groups and unsaturated groups.

[0009] Preferably, the cross-linking agent includes at least one of acrylamide, N,N-methylenebisacrylamide and polyethylene glycol-biscarbamate dimethacrylate; and the polymerizable monomer is a polyethylene glycol-based acrylate monomer.

[0010] Preferably, the polyethylene glycol acrylate monomer includes at least one of methoxy polyethylene glycol acrylate, ethylene glycol monomethyl ether acrylate and polyethylene glycol methyl ether methacrylate;

[0011] The number average molecular weight of the methoxy polyethylene glycol acrylate is 480-10000; the number average molecular weight of the polyethylene glycol methyl ether methacrylate is 300-4000.

[0012] Preferably, the unsaturated zwitterionic compound comprises at least one of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, 2-methacryloyloxyethylphosphocholine and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate;

[0013] The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate, lithium difluorophosphate and lithium difluorooxalatoborate; the plasticizer includes at least one of ethylene carbonate, propylene carbonate, tetraethylene glycol dimethyl ether, 1-n-butyl-3-methylimidazolium hexafluorophosphate and 1-allyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide;

[0014] The initiator includes at least one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methyl-1-phenylpropanone and 1-hydroxycyclohexylphenylketone.

[0015] The invention provides an unsaturated zwitterion-based polymer membrane, comprising a base membrane and a polymer loaded on the base membrane; the polymer is the unsaturated zwitterion-based polymer described in the above technical solution.

[0016] Preferably, the base membrane is a polyethylene membrane, a polypropylene membrane, a cellulose membrane, a glass fiber membrane, a polyvinylidene fluoride membrane or a polyacrylonitrile membrane; and the loading amount of the polymer on the unsaturated zwitterionic polymer membrane is 85% to 95%.

[0017] The present invention provides a method for preparing the unsaturated zwitterion-based polymer membrane described in the above technical solution, comprising the following steps:

[0018] The base film is immersed in a precursor solution for immersion treatment, and the obtained immersed base film is subjected to light irradiation to in-situ polymerize the base film to generate an unsaturated zwitterionic polymer to obtain the unsaturated zwitterionic polymer film; the precursor solution includes the raw materials for preparing the unsaturated zwitterionic polymer described in the above technical solution.

[0019] Preferably, the immersion treatment time is 10 to 20 minutes; the light source of the light irradiation is ultraviolet light, and the wavelength of the ultraviolet light is 200 to 380 nm; the light irradiation time is 10 to 60 minutes, and the light intensity of the light irradiation is 50 to 200 mW / cm 2 .

[0020] The present invention provides the use of the unsaturated zwitterion-based polymer described in the above technical solution, the unsaturated zwitterion-based polymer film described in the above technical solution, or the unsaturated zwitterion-based polymer film obtained by the preparation method described in the above technical solution as a solid electrolyte in a lithium ion battery.

[0021] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte; the solid electrolyte is the unsaturated zwitterion-based polymer described in the above technical solution, the unsaturated zwitterion-based polymer film described in the above technical solution or the unsaturated zwitterion-based polymer film obtained by the preparation method described in the above technical solution.

[0022] The present invention provides an unsaturated zwitterionic polymer, which includes the following raw materials by weight: 40-70 parts of polymerized monomers, 0.1-1 parts of crosslinking agents, 1-10 parts of unsaturated zwitterionic compounds, 20-30 parts of lithium salts, 5-20 parts of plasticizers, and 0.1-1 parts of initiators; the crosslinking agent contains imino groups and unsaturated groups. In the present invention, the imino groups in the crosslinking agent have a strong ability to form hydrogen bonds, and there are groups (COC) that can form hydrogen bonds in the structures of the unsaturated zwitterionic compounds and polymerized monomers, thereby forming physical crosslinking points with the unsaturated zwitterionic compounds and polymerized monomers, forming dynamic hydrogen bonds, and improving the mechanical properties of the unsaturated zwitterionic polymer; at the same time, the obtained unsaturated zwitterionic polymer can have a certain viscoelasticity and can withstand the volume change of the lithium negative electrode during the operation of the lithium ion battery. At the same time, the polymerized monomers, unsaturated zwitterionic compounds, and plasticizers form a main chain through a polymerization reaction, and the positive charge center of the zwitterionic compound interacts with the anion in the lithium salt to limit the migration of the anion and promote the Li + The migration of anions and Li + The joint regulation of Li +The unsaturated zwitterion-based polymer prepared on this basis can construct a unique zwitterion nanochannel through the synergistic effect of ion-dipole interaction and dynamic hydrogen bonding, resulting in uniform deposition of lithium ions. The dynamic network energy dissipation is beneficial to the anti-puncture of lithium dendrites, thereby effectively inhibiting the growth of lithium dendrites. Furthermore, the present invention uses unsaturated zwitterions and anions in lithium salts, Li + The ion-dipole interaction between the cations in the plasticizer (ionic liquid) constructs the nanochannel of unsaturated zwitterions. Specifically, the ion-dipole interaction can adjust the arrangement of polymer segments and act as an ion transport channel to promote ion transport. The introduction of ionic liquid promotes the dissociation of lithium salts, thereby improving Li + The ether oxygen segments in the polymerized monomers promote the transport of Li + The synergistic effect of the three can accelerate the transmission of lithium ions, improve the ionic conductivity, and thus make the obtained unsaturated zwitterionic polymer have higher ionic conductivity, wider electrochemical window and excellent thermal stability. When the unsaturated zwitterionic polymer of the present invention is used as the electrolyte of lithium ion battery, it is beneficial to improve the rate performance and cycle performance of lithium ion battery.

[0023] The present invention provides an unsaturated zwitterion-based polymer membrane, comprising a base membrane and an unsaturated zwitterion-based polymer loaded on the base membrane. In the present invention, the base membrane plays a supporting role, so that the unsaturated zwitterion-based polymer can be covered on the base membrane, the mechanical properties of the unsaturated zwitterion-based polymer membrane are improved, and the anti-dendritic ability of the unsaturated zwitterion-based polymer membrane is improved; the carbon-carbon double bonds and imino groups of the crosslinking agent in the unsaturated zwitterion-based polymer can form chemical crosslinking points and physical crosslinking points between the unsaturated zwitterion compound and the polymerized monomer, so that the obtained unsaturated zwitterion-based polymer membrane has a certain viscoelasticity, and when it is assembled into a lithium-ion battery as a solid electrolyte, it can withstand the volume change of the lithium negative electrode during the operation of the lithium-ion battery. The unsaturated zwitterion-based polymer membrane provided by the present invention has high ionic conductivity, wide electrochemical window, superior thermal stability and excellent interface compatibility, and can be used in a wide temperature range. The results of the embodiment show that the room temperature ionic conductivity of the unsaturated zwitterion-based polymer membrane provided by the present invention is 5.35×10 -5 ~12.8×10 -5 S / cm -1 , the anti-oxidation potential is 4.9~5.0V, and the lithium ion migration number is 0.29~0.53.

[0024] The present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte; the solid electrolyte is the unsaturated zwitterion-based polymer or the unsaturated zwitterion-based polymer membrane described in the above technical solution. In the embodiment of the present invention, a 2025-type button-type lithium-ion battery (LFP / / Li battery) is assembled using an unsaturated zwitterion-based polymer membrane, and the LFP / / Li battery is subjected to charge and discharge cycles at different rates at 25°C using a Xinwei battery circulation system. The results show that at room temperature, at a rate of 0.1C, the specific capacity of the LFP / / Li battery is 159mAh / g; at a rate of 0.2C, the specific capacity of the LFP / / Li battery is 158mAh / g; at a rate of 0.5C, the specific capacity of the LFP / / Li is 152mAh / g. g; at 1C rate, the specific capacity of the LFP / / Li battery is 143mAh / g; at 2C rate, the specific capacity of the LFP / / Li battery is 124mAh / g, and when it returns to 1C, 0.5C and 0.2C rates, the specific capacity of the LFP / / Li battery can still reach 145mAh / g, 151mAh / g and 154mAh / g respectively; at 0.5C high rate, the first cycle discharge capacity of the LFP / / Li battery is 143.77mAh / g, and after 735 cycles, the capacity retention rate is 91%. It can be seen that the lithium ion battery of the present invention has excellent rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 This is a SEM image of the unsaturated zwitterion-based polymer membrane prepared in Example 1;

[0027] Figure 2 The temperature-dependent impedance diagram of the unsaturated zwitterion-based polymer membrane prepared in Example 1;

[0028] Figure 3 The linear sweep voltammetry curve of the unsaturated zwitterion-based polymer film prepared in Example 1;

[0029] Figure 4 The thermogravimetric curve of the unsaturated zwitterion-based polymer membrane prepared in Example 1;

[0030] Figure 5 is a stress-strain curve diagram of the unsaturated zwitterion-based polymer membrane obtained in Example 1;

[0031] Figure 6 It curve of Li / / Li symmetric battery prepared based on unsaturated zwitterionic polymer and impedance spectrum before and after battery polarization;

[0032] Figure 7 The Li / / Li symmetric battery based on unsaturated zwitterionic polymer was prepared at a current density of 0.1 mA cm -2 The voltage variation curve at time ;

[0033] Figure 8 This is the rate cycle diagram of the LFP / unsaturated zwitterionic polymer / Li battery assembled in Example 2. DETAILED DESCRIPTION

[0034] The present invention provides an unsaturated zwitterionic polymer, which comprises the following raw materials by weight:

[0035] 40-70 parts of polymerizable monomers, 0.1-1 parts of crosslinking agents, 1-10 parts of unsaturated zwitterionic compounds, 20-30 parts of lithium salts, 5-20 parts of plasticizers and 0.1-1 parts of initiators; the crosslinking agent contains imino groups and unsaturated groups.

[0036] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.

[0037] In terms of mass fractions, the raw materials for preparing the unsaturated zwitterionic polymer of the present invention include 40 to 70 parts of polymerized monomers; in a specific embodiment of the present invention, the mass fractions of the polymerized monomers are 40, 50, 60 or 70 parts. In the present invention, the polymerized monomers may be polyethylene glycol acrylate monomers; the polyethylene glycol acrylate monomers may include at least one of methoxy polyethylene glycol acrylate, ethylene glycol monomethyl ether acrylate and polyethylene glycol methyl ether methacrylate. In a specific embodiment of the present invention, the polymerized monomers are methoxy polyethylene glycol acrylate, ethylene glycol monomethyl ether acrylate or polyethylene glycol methyl ether methacrylate. The number average molecular weight of the methoxy polyethylene glycol acrylate of the present invention may be 480 to 10,000; in a specific embodiment of the present invention, the number average molecular weight of the methoxy polyethylene glycol acrylate is 480, 1,000 or 2,000. The number average molecular weight of the polyethylene glycol methyl ether methacrylate of the present invention can be 300 to 4000; in a specific embodiment of the present invention, the number average molecular weight of the polyethylene glycol methyl ether methacrylate is 300, 950 or 2000. In the present invention, the polymerized monomer, the unsaturated zwitterionic compound and the plasticizer form a main chain through a polymerization reaction, and the positive charge center of the zwitterionic compound interacts with the anion in the lithium salt to limit the migration of the anion and promote the Li +The migration of anions and Li + The joint regulation of Li + uniform deposition; the unsaturated zwitterionic polymers prepared on this basis can construct unique zwitterionic nanochannels through the synergistic effect of ion-dipole interaction and dynamic hydrogen bonding, resulting in uniform deposition of lithium ions. The dynamic network energy dissipation is beneficial to the anti-puncture of lithium dendrites, thereby effectively inhibiting the growth of lithium dendrites.

[0038] Based on the mass fraction of the polymerized monomer, the raw material for preparing the unsaturated zwitterionic polymer of the present invention includes 0.1 to 1 part of a crosslinking agent; in a specific embodiment of the present invention, the mass fraction of the crosslinking agent is 0.2 part, 0.3 part, 0.6 part, 0.8 part or 1 part. In the present invention, the crosslinking agent contains an imino group and an unsaturated group; the crosslinking agent may include at least one of acrylamide, N,N-methylenebisacrylamide and polyethylene glycol-biscarbamate dimethacrylate; in a specific embodiment of the present invention, the crosslinking agent is acrylamide, N,N-methylenebisacrylamide or polyethylene glycol-biscarbamate dimethacrylate. In the present invention, the NH bonds in the cross-linking agent can form hydrogen bonds, and there are groups (COC) that can form hydrogen bonds in the structures of the unsaturated zwitterionic compound and the polymerized monomer, so that physical cross-linking points can be formed between the unsaturated zwitterionic compound and the polymerized monomer, forming dynamic hydrogen bonds, which can improve the mechanical properties of the unsaturated zwitterionic polymer; at the same time, the obtained unsaturated zwitterionic polymer can have a certain viscoelasticity and can withstand the volume change of the lithium negative electrode during the operation of the lithium-ion battery.

[0039] Based on the mass fraction of the polymerized monomer, the raw material for preparing the unsaturated zwitterionic polymer of the present invention includes 1 to 10 parts of unsaturated zwitterionic compounds; in a specific embodiment of the present invention, the mass fraction of the unsaturated zwitterionic compounds is 1 part, 3 parts, 5 parts, 7 parts or 10 parts. In the present invention, the unsaturated zwitterionic compound may include at least one of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide, 2-methacryloyloxyethyl phosphorylcholine and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate; in a specific embodiment of the present invention, the unsaturated zwitterionic compound is [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide, 2-methacryloyloxyethyl phosphorylcholine or 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate. The present invention combines the unsaturated zwitterionic compound and the anion, Li in the lithium salt +, the ion-dipole interaction between the cations in the ionic liquid constructs the nanochannel of unsaturated zwitterions. Specifically, the ion-dipole interaction can adjust the arrangement of the polymer segments, acting as an ion transport channel to promote ion transport. The introduction of the plasticizer (ionic liquid) promotes the dissociation of the lithium salt, thereby improving the Li + The ether oxygen segments in the polymerized monomers promote the transport of Li + The synergistic effect of the three can accelerate the transmission of lithium ions and improve the ionic conductivity, so that the obtained unsaturated zwitterionic polymer has higher ionic conductivity, wider electrochemical window and excellent thermal stability. Among them, the thermal stability data of the unsaturated zwitterionic polymer is as high as 300℃.

[0040] Based on the mass fraction of the polymerized monomer, the raw material for preparing the unsaturated zwitterionic polymer of the present invention includes 20 to 30 parts of lithium salt; in a specific embodiment of the present invention, the mass fraction of the lithium salt is 20 parts, 23 parts, 26 parts or 30 parts. In the present invention, the lithium salt may include at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium nitrate, lithium difluorophosphate and lithium difluorooxalate borate; in a specific embodiment of the present invention, the lithium salt is a mixture of lithium bis(trifluoromethylsulfonyl)imide and lithium difluorooxalate borate. In the present invention, when the lithium salt is a mixture of lithium bis(trifluoromethylsulfonyl)imide and lithium difluorooxalate borate, the mass ratio of lithium bis(trifluoromethylsulfonyl)imide to lithium difluorooxalate borate can be 8 to 10:1. The present invention has no special limitation on the source of the lithium salt, and commercially available products known to those skilled in the art can be used.

[0041] Based on the mass fraction of the polymerized monomer, the raw material for preparing the unsaturated zwitterionic polymer of the present invention includes 5 to 20 parts of a plasticizer; in a specific embodiment of the present invention, the mass fraction of the plasticizer is 5 parts, 10 parts, 15 parts or 20 parts. In the present invention, the plasticizer may include at least one of ethylene carbonate, propylene carbonate, tetraethylene glycol dimethyl ether, 1-n-butyl-3-methylimidazolium hexafluorophosphate and 1-allyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide; in a specific embodiment of the present invention, the plasticizer is ethylene carbonate, propylene carbonate, tetraethylene glycol dimethyl ether, 1-n-butyl-3-methylimidazolium hexafluorophosphate or 1-allyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide. In the present invention, the molar ratio of the unsaturated zwitterionic compound to the plasticizer can be 1:2 to 16; in a specific embodiment of the present invention, the molar ratio of the unsaturated zwitterionic compound to the plasticizer is 1:2, 1:4, 1:6, 1:10 or 1:16. In the present invention, the plasticizer is an ionic liquid, which is non-volatile, can promote the movement of polymer segments and the dissociation of lithium salts, and can significantly improve the ionic conductivity without affecting safety; the present invention limits the molar ratio of the unsaturated zwitterionic compound to the plasticizer within the above range, which can promote the construction of unsaturated zwitterionic nanochannels, accelerate the transmission of lithium ions, and thus improve the ionic conductivity.

[0042] Based on the mass fraction of the polymerized monomer, the raw material for preparing the unsaturated zwitterionic polymer of the present invention includes 0.1 to 1 parts of initiator; in a specific embodiment of the present invention, the mass fraction of the initiator is 0.1 parts, 0.3 parts, 0.6 parts, 0.8 parts or 1 parts. The initiator of the present invention can be a photoinitiator. In the present invention, the initiator can include at least one of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 2-hydroxy-2-methyl-1-phenyl acetone and 1-hydroxycyclohexyl phenyl ketone; in a specific embodiment of the present invention, the initiator is phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, 2-hydroxy-2-methyl-1-phenyl acetone or 1-hydroxycyclohexyl phenyl ketone.

[0043] The main chain segment of the unsaturated zwitterionic polymer of the present invention is ether oxygen, wherein the number of repeating units of ether oxygen is 9.

[0044] The unsaturated zwitterionic polymer of the present invention has high ionic conductivity and a wide electrochemical window, and has excellent thermal stability; when it is used as an electrolyte of a lithium ion battery, it is beneficial to improve the rate performance and cycle performance of the lithium ion battery.

[0045] The present invention also provides an unsaturated zwitterion-based polymer membrane, comprising a base membrane and a polymer loaded on the base membrane; the polymer is the unsaturated zwitterion-based polymer described in the above technical solution.

[0046] In the present invention, the base film can be a polyethylene film (PE), a polypropylene film (PP), a cellulose film, a glass fiber film, a polyvinylidene fluoride (PVDF) membrane or a polyacrylonitrile (PAN) membrane; in a specific embodiment of the present invention, the base film can be a cellulose film or a glass fiber membrane. In the present invention, the base film plays a supporting role, allowing the unsaturated zwitterion-based polymer to cover the base film, improving the mechanical properties of the unsaturated zwitterion-based polymer film, and improving the anti-dendritic ability of the unsaturated zwitterion-based polymer film. Furthermore, the present invention uses a base film with a large porosity, which allows the precursor solution to fully penetrate into the base film.

[0047] In the present invention, the loading amount of the polymer on the unsaturated zwitterion-based polymer membrane may be 85% to 95%; in a specific embodiment of the present invention, the loading amount of the polymer on the unsaturated zwitterion-based polymer membrane is 85%, 90% or 95%.

[0048] In the present invention, the thickness of the unsaturated zwitterion-based polymer membrane may be 30 to 80 μm; in a specific embodiment of the present invention, the thickness of the unsaturated zwitterion-based polymer membrane is 30 μm, 50 μm or 80 μm.

[0049] The unsaturated zwitterion-based polymer membrane provided by the present invention has high ionic conductivity, wide electrochemical window, superior thermal stability and excellent interface compatibility, and can be used in a wide temperature range. The results of the examples show that the room temperature ionic conductivity of the unsaturated zwitterion-based polymer membrane provided by the present invention is 5.35×10 -5 ~12.8×10 -5 S / cm -1 , the anti-oxidation potential is 4.9~5.0V, and the lithium ion migration number is 0.29~0.53.

[0050] The present invention also provides a method for preparing the unsaturated zwitterion-based polymer membrane described in the above technical solution, comprising the following steps:

[0051] The base film is immersed in a precursor solution for immersion treatment, and the obtained immersed base film is subjected to light irradiation to in-situ polymerize the base film to generate an unsaturated zwitterionic polymer to obtain the unsaturated zwitterionic polymer film; the precursor solution includes the raw materials for preparing the unsaturated zwitterionic polymer described in the above technical solution.

[0052] In the present invention, the preparation method of the precursor solution comprises the following steps: a first mixing of a polymerizable monomer, a crosslinking agent, an unsaturated zwitterionic compound, a lithium salt and a plasticizer to obtain a first material; a second mixing of an initiator and the first material to obtain the precursor solution. The temperature of the first mixing of the present invention may be 25 to 40°C; in a specific embodiment of the present invention, the temperature of the first mixing is 25°C, 26°C or 30°C. In the present invention, the first mixing may be carried out under stirring, and the stirring may be mechanical stirring; the stirring speed may be 300 to 500 rpm, and the time may be 2 to 4 hours. In a specific embodiment of the present invention, when the first mixing is carried out, the stirring speed is 300 rpm, 400 rpm or 500 rpm; the time is 2 hours, 3 hours or 4 hours. The temperature of the second mixing of the present invention may be 25 to 40°C; in a specific embodiment of the present invention, the temperature of the second mixing is 25°C, 26°C or 30°C. In the present invention, the second mixing can be performed under stirring conditions, and the stirring can be mechanical stirring; the stirring speed can be 300-500 rpm, and the time can be 1-2 hours. In a specific embodiment of the present invention, when the second mixing is performed, the stirring speed is 300 rpm, 400 rpm or 500 rpm; the time is 1 hour, 1.5 hours or 2 hours. The present invention can make the components mixed more uniformly by controlling the stirring speed, temperature and time.

[0053] The concentration of lithium salt in the precursor solution of the present invention can be 1-5 mol / L; in a specific embodiment of the present invention, the concentration of lithium salt in the precursor solution is 1 mol / L, 1.5 mol / L or 3 mol / L. The present invention limits the concentration of lithium salt to the above range, which can increase the content of lithium salt in the unsaturated zwitterionic polymer and avoid low ion conductivity due to less lithium salt.

[0054] After obtaining the precursor solution, the present invention immerses the base film in the precursor solution for immersion treatment to obtain an impregnated base film. In the present invention, the temperature of the immersion treatment can be 20 to 35°C, and the time can be 10 to 20 minutes; in a specific embodiment of the present invention, the temperature of the immersion treatment is 20°C, 25°C, 30°C or 35°C, and the time is 10 minutes, 15 minutes or 20 minutes. The present invention transfers the raw materials for preparing the unsaturated zwitterionic polymer to the base film through immersion treatment.

[0055] After obtaining the impregnated base film, the present invention sandwiches the impregnated base film between two glass plates and irradiates the base film with light to polymerize the base film in situ to generate unsaturated zwitterionic polymers. In the present invention, the light source of the light irradiation can be ultraviolet light, the wavelength of the ultraviolet light can be 200 to 380 nm; the light irradiation time can be 10 to 60 minutes, and the light intensity of the light irradiation can be 50 to 200 mW / cm 2 In a specific embodiment of the present invention, the wavelength of the ultraviolet light is 365nm; the light irradiation time is 10min, 15min, 20min, 30min or 60min; the light intensity of the light irradiation is 50mW / cm 2 , 100mW / cm 2 、150mW / cm 2 or 200mW / cm 2 The present invention limits the light source, wavelength, time and light intensity of the light irradiation within the above range, which can make the cross-linking reaction proceed more fully and further improve the electrochemical performance of the obtained product. In the present invention, after the light irradiation is completed, the glass plate is removed to obtain the unsaturated zwitterion-based polymer film.

[0056] The present invention also provides the use of the unsaturated zwitterion-based polymer described in the above technical solution, the unsaturated zwitterion-based polymer film described in the above technical solution, or the unsaturated zwitterion-based polymer film obtained by the preparation method described in the above technical solution as a solid electrolyte in a lithium ion battery.

[0057] The present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte; the solid electrolyte is the unsaturated zwitterion-based polymer described in the above technical solution, the unsaturated zwitterion-based polymer film described in the above technical solution or the unsaturated zwitterion-based polymer film obtained by the preparation method described in the above technical solution.

[0058] In the present invention, the solid electrolyte may be between the positive electrode and the negative electrode. In the present invention, the positive electrode may include a lithium iron phosphate (LFP) material or a nickel-cobalt-manganese ternary material; the nickel-cobalt-manganese ternary material may be NCM811 or NCM622. In a specific embodiment of the present invention, the positive electrode is a lithium iron phosphate material. The preparation method of the lithium iron phosphate material of the present invention may include the following steps: mixing lithium iron phosphate, carbon black, polyvinylidene fluoride and an organic solvent, stirring to obtain a slurry; coating the slurry on an aluminum material, and drying the obtained material to obtain a lithium iron phosphate material. In the present invention, the mass ratio of lithium iron phosphate, carbon black and polyvinylidene fluoride may be 80:10:10; the organic solvent includes N-methylpyrrolidone. The stirring of the present invention may be magnetic stirring; the stirring time may be 24h. The drying temperature of the present invention may be 120°C, and the time may be 24h. The diameter of the lithium iron phosphate material of the present invention may be 13mm. In the present invention, the negative electrode may include a metal material, a graphite material or a silicon-based material; the metal material of the present invention may be a lithium sheet or a zinc sheet. The graphite material of the present invention may be graphite or carbon nanotubes; the graphite may be natural graphite or artificial graphite. The silicon-based material of the present invention may be a silicon single substance material or a silicon compound material; the silicon compound material may be a silicon-carbon composite material.

[0059] In the present invention, the lithium ion battery may be a button battery; the button battery may be a 2025 type button battery. The present invention has no particular limitation on the preparation method of the lithium ion battery, and the technical solution for preparing lithium ion batteries well known to those skilled in the art may be used.

[0060] In a specific embodiment of the present invention, LFP material is used as the positive electrode plate, Li plate is used as the negative electrode plate, and unsaturated zwitterionic polymer film is used as the solid electrolyte; the solid electrolyte is placed between the positive electrode plate and the negative electrode plate, and a 2025 type button battery (LFP / / Li battery) is assembled. The present invention uses the Xinwei battery circulation system to perform charge and discharge cycles at different rates on the LFP / / Li battery at 25°C. The results show that at room temperature, the specific capacity of the LFP / / Li battery at a rate of 0.1C is 159mAh / g; at a rate of 0.2C, the specific capacity of the LFP / / Li battery is 158mAh / g; at a rate of 0.5C, the specific capacity of the LFP / / Li battery is 152mAh / g; at a rate of 1C, the specific capacity of the LFP / / Li battery is 14 3mAh / g; at 2C rate, the specific capacity of LFP / / Li battery is 124mAh / g, and when it returns to 1C, 0.5C and 0.2C rate, the specific capacity of LFP / / Li battery can still reach 145mAh / g, 151mAh / g and 154mAh / g respectively; at 0.5C high rate, the first cycle discharge capacity of LFP / / Li battery is 143.77mAh / g, and after 735 cycles, the capacity retention rate is 91%. It can be seen that the lithium-ion battery assembled with the unsaturated zwitterionic polymer membrane as solid electrolyte has excellent rate performance and cycle stability.

[0061] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] The number average molecular weight of the methoxy polyethylene glycol acrylate used in the examples is 480, purchased from Aladdin Biochemical Technology Co., Ltd.;

[0063] The cellulose membrane used in the examples was purchased from Liaoyuan Hongtu Lithium Battery Membrane Technology Co., Ltd.

[0064] Example 1

[0065] 480 mg of methoxy polyethylene glycol acrylate, 2.1 mg of N,N-methylenebisacrylamide, 11.5 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate, 121.9 mg of 1-allyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 196.5 mg of lithium bis(trifluoromethanesulfonylimide) and 19.7 mg of lithium difluorooxalatoborate were mixed, and the mixture was stirred at 400 rpm for 4 h at 25 ° C to obtain a first material; 4 mg of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added to the first material, and the mixture was stirred at 400 rpm for 1 h at 25 ° C to obtain a precursor solution.

[0066] A cellulose membrane with a diameter of 16 mm was immersed in the precursor solution for 10 minutes to obtain an impregnated cellulose membrane; the impregnated cellulose membrane was sandwiched between two glass plates and illuminated at a wavelength of 365 nm and a light intensity of 150 mW / cm 2 After irradiation for 20 min under ultraviolet light, the glass plate was removed, and the unsaturated zwitterion-based polymer was loaded on the base film to obtain an unsaturated zwitterion-based polymer film with a thickness of 39 μm.

[0067] Figure 1 The SEM image of the unsaturated zwitterionic polymer membrane prepared in Example 1 is shown in FIG. Figure 1 It can be seen that the surface of the unsaturated zwitterion-based polymer membrane prepared in Example 1 has obvious texture, indicating that the obtained polymer is a polymer with a cross-linked network structure; combined with the performance test results, it can be seen that the linear macromolecules are cross-linked and transformed into a three-dimensional network structure, which can improve the strength, heat resistance and chemical stability of the unsaturated zwitterion-based polymer membrane.

[0068] The conductivity of the unsaturated zwitterionic polymer membrane obtained in Example 1 was tested under different temperatures (30-80° C.). The trend of the conductivity versus temperature is shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the unsaturated zwitterionic polymer membrane prepared in Example 1 has good ionic conductivity at different temperatures, and the ionic conductivity can reach 1.28×10 -4 S cm -1 .

[0069] The electrochemical window of the unsaturated zwitterion-based polymer membrane obtained in Example 1 is as follows: Figure 3 As shown. Figure 3 It can be seen that the anti-oxidation potential of the unsaturated zwitterion-based polymer membrane prepared in Example 1 is 5.0V.

[0070] The thermogravimetric curve of the unsaturated zwitterionic polymer membrane obtained in Example 1 is as follows: Figure 4 As shown. Figure 4 It can be seen that the unsaturated zwitterion-based polymer membrane begins to decompose at 300°C, which is conducive to the use of the unsaturated zwitterion-based polymer membrane in a wider temperature range.

[0071] The stress-strain curve of the unsaturated zwitterionic polymer membrane obtained in Example 1 is shown in Figure 5 As shown. Figure 5 It can be seen that the stress of the unsaturated zwitterionic polymer film is 3.36 MPa and the strain is 9.1%.

[0072] The unsaturated zwitterionic polymer film obtained in Example 1 was used as the electrolyte, and lithium sheets were used as the positive electrode sheet and the negative electrode sheet to assemble a Li / / Li symmetrical battery.

[0073] The It curve of the Li / / Li symmetric battery prepared based on the unsaturated zwitterionic polymer membrane and the impedance results before and after battery polarization are shown in Figure 2. Figure 6 As shown. Figure 6 It can be seen that the lithium ion transfer number of the unsaturated zwitterion-based polymer membrane prepared in Example 1 at room temperature is 0.53.

[0074] The voltage variation curve of the Li / / Li symmetric battery prepared based on unsaturated zwitterionic polymer membrane under constant current conditions is shown in the figure. Figure 7 As shown. Figure 7 It can be seen that the unsaturated zwitterionic polymer membrane can be used at 0.1 mA cm -2 Lithium plating and stripping can be stably carried out under the above conditions and can last for 2000 h, and the overpotential is reduced from the initial 39 mV to 13 mV, which confirms that the unsaturated zwitterionic polymer membrane prepared in Example 1 has good interfacial compatibility.

[0075] Example 2

[0076] Add 80% of the positive electrode active material lithium iron phosphate (LFP), 10% of carbon black and 10% of polyvinylidene fluoride (PVDF, as a binder) to N-methylpyrrolidone and stir magnetically for 24 hours to form a viscous slurry; coat the slurry on aluminum foil and place it in a vacuum drying oven and vacuum dry it at 120°C for 24 hours; after drying, adjust the temperature to room temperature and cut the obtained material into a circular pole piece with a diameter of 13mm to obtain a positive pole piece. Assemble the unsaturated zwitterionic polymer membrane (as a solid electrolyte) with the positive pole piece and the negative pole piece (lithium sheet) into a 2025 button battery (LFP / unsaturated zwitterionic polymer membrane / Li battery, referred to as LFP / / Li battery).

[0077] At 25°C, the LFP / / Li battery was tested for charge and discharge cycles at different rates using the Xinwei battery cycling system. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that at room temperature and 0.1C rate, the specific capacity of LFP / / Li battery is 159mAh / g; at 0.2C rate, the specific capacity of LFP / / Li battery is 158mAh / g; at 0.5C rate, the specific capacity of LFP / / Li battery is 152mAh / g; at 1C rate, the specific capacity of LFP / / Li battery is 143mAh / g; at 2C rate, the specific capacity of LFP / / Li battery is 124mAh / g; when returning to 1C, 0.5C, and 0.2C rates respectively, the specific capacity of LFP / / Li battery can still reach 145mAh / g, 151mAh / g, and 154mAh / g respectively, which shows that the obtained button battery has excellent rate performance.

[0078] The LFP / unsaturated zwitterionic polymer membrane / Li battery assembled in Example 2 has a first-cycle discharge capacity of 143.77 mAh / g at a high rate of 0.5 C, and a capacity retention rate of 91% after 735 cycles.

[0079] Example 3

[0080] 480 mg of methoxy polyethylene glycol acrylate, 2.1 mg of N,N-methylenebisacrylamide, 11.5 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate, 81.3 mg of 1-allyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 186.2 mg of lithium bis(trifluoromethanesulfonylimide) and 18.6 mg of lithium difluorooxalatoborate were mixed, and the mixture was stirred at 400 rpm for 4 h at 25 ° C to obtain a first material; 4 mg of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added to the first material, and the mixture was stirred at 400 rpm for 1 h at 25 ° C to obtain a precursor solution.

[0081] A cellulose membrane with a diameter of 16 mm was immersed in the precursor solution for 10 minutes to obtain an impregnated cellulose membrane; the impregnated cellulose membrane was sandwiched between two glass plates and illuminated at a wavelength of 365 nm and a light intensity of 150 mW / cm 2 After irradiation for 20 min under ultraviolet light, the glass plate was removed, and the unsaturated zwitterion-based polymer was loaded on the base film to obtain an unsaturated zwitterion-based polymer film with a thickness of 41 μm.

[0082] The conductivity, lithium ion migration number and antioxidant potential of the unsaturated zwitterionic polymer membrane prepared in Example 3 were tested according to the conditions of Example 1. The results showed that the room temperature ionic conductivity of the unsaturated zwitterionic polymer membrane prepared in Example 3 was 6.55×10 -5 S cm -1, the lithium ion migration number at room temperature is 0.49, and the anti-oxidation potential is 4.9V.

[0083] Example 4

[0084] 480 mg of methoxy polyethylene glycol acrylate, 2.1 mg of N,N-methylenebisacrylamide, 11.5 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate, 162.5 mg of 1-allyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 206.8 mg of lithium bis(trifluoromethanesulfonylimide) and 20.68 mg of lithium difluorooxalatoborate were mixed, and the mixture was stirred at 400 rpm for 4 h at 25 ° C to obtain a first material; 4 mg of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added to the first material, and the mixture was stirred at 400 rpm for 1 h at 25 ° C to obtain a precursor solution.

[0085] A cellulose membrane with a diameter of 16 mm was immersed in the precursor solution for 10 minutes to obtain an impregnated cellulose membrane; the impregnated cellulose membrane was sandwiched between two glass plates and illuminated at a wavelength of 365 nm and a light intensity of 150 mW / cm 2 After irradiation for 20 min under ultraviolet light, the glass plate was removed, and the unsaturated zwitterion-based polymer was loaded on the base film to obtain an unsaturated zwitterion-based polymer film with a thickness of 40 μm.

[0086] The conductivity, lithium ion migration number and antioxidant potential of the unsaturated zwitterionic polymer membrane prepared in Example 4 were tested according to the conditions of Example 1. The results showed that the room temperature ionic conductivity of the unsaturated zwitterionic polymer membrane prepared in Example 4 was 5.35×10 -5 S cm -1 The lithium ion migration number at room temperature is 0.29 and the anti-oxidation potential is 4.95V.

[0087] Comparative Example 1

[0088] 480 mg of methoxy polyethylene glycol acrylate, 2.1 mg of N,N-methylenebisacrylamide, 11.5 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate, 165.6 mg of lithium bistrifluoromethylsulfonyl imide and 16.56 mg of lithium difluorooxalatoborate were mixed, and the mixture was stirred at 400 rpm for 4 hours at 25° C. to obtain a first material; 4 mg of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added to the first material, and the mixture was stirred at 400 rpm for 1 hour at 25° C. to obtain a precursor solution.

[0089] A cellulose membrane with a diameter of 16 mm was immersed in the precursor solution for 10 minutes to obtain an impregnated cellulose membrane; the impregnated cellulose membrane was sandwiched between two glass plates and illuminated at a wavelength of 365 nm and a light intensity of 150 mW / cm 2 The film was irradiated under ultraviolet light for 20 min, and the glass plate was removed after irradiation to obtain a polymer film with a thickness of 40 μm.

[0090] The conductivity and lithium ion migration number of the polymer membrane prepared in Comparative Example 1 were tested according to the conditions of Example 1. The results showed that the room temperature ionic conductivity of the polymer membrane prepared in Comparative Example 1 was 3.15×10 -5 S cm -1 , the lithium ion migration number at room temperature is 0.38, the conductivity is low, the interface impedance is large, and the charge and discharge capacity of the button battery at room temperature is low, only about 30mAh / g. This is due to the low ion conductivity, which leads to the Li + The transmission between the positive and negative electrodes becomes difficult; the large interface impedance will cause the power attenuation of the button battery, thereby reducing the available capacity of the button battery; in addition, the uncontrollable dendrite growth will cause a large volume expansion and low reversibility, and the local ion depletion to form a space charge layer (SCL) will also accelerate the growth of Li dendrites.

[0091] Comparative Example 2

[0092] 480 mg of methoxy polyethylene glycol acrylate, 2.1 mg of N,N-methylenebisacrylamide, 121.9 mg of 1-allyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 161.5 mg of lithium bis(trifluoromethanesulfonyl)imide and 16.15 mg of lithium difluorooxalate borate were mixed, and stirred at 400 rpm for 4 hours at 25° C. to obtain a first material; 4 mg of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide was added to the first material, and stirred at 400 rpm for 1 hour at 25° C. to obtain a precursor solution.

[0093] A cellulose membrane with a diameter of 16 mm was immersed in the precursor solution for 10 minutes to obtain an impregnated cellulose membrane; the impregnated cellulose membrane was sandwiched between two glass plates and illuminated at a wavelength of 365 nm and a light intensity of 150 mW / cm 2 The film was irradiated under ultraviolet light for 20 min, and the glass plate was removed after irradiation to obtain a polymer film with a thickness of 50 μm.

[0094] The conductivity and lithium ion migration number of the polymer membrane prepared in Comparative Example 2 were tested according to the conditions of Example 1. The results showed that the room temperature ionic conductivity of the polymer membrane prepared in Comparative Example 2 was 8.63×10 -5 S cm -1, the lithium ion migration number at room temperature is 0.33. This is because the lack of zwitterions allows both anions and lithium ions in the button battery to move freely, which in turn leads to a decrease in the lithium ion migration number; and the addition of plasticizers can promote the movement of polymer chains and the dissociation of lithium salts, thereby improving ionic conductivity.

[0095] In summary, the unsaturated zwitterion-based polymer membrane provided by the present invention has high room temperature ionic conductivity, a wide electrochemical window and excellent thermal stability. The lithium iron phosphate battery assembled using the unsaturated zwitterion-based polymer membrane as a solid electrolyte has excellent rate performance and cycle performance.

[0096] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An unsaturated zwitterionic polymer, characterized in that: The preparation includes the following raw materials by weight: 40-70 parts of polymerizable monomers, 0.1-1 parts of crosslinking agents, 1-10 parts of unsaturated zwitterionic compounds, 20-30 parts of lithium salts, 5-20 parts of plasticizers and 0.1-1 parts of initiators; the crosslinking agent contains imino groups and unsaturated groups.

2. The unsaturated zwitterionic polymer according to claim 1, characterized in that The cross-linking agent includes at least one of acrylamide, N,N-methylenebisacrylamide and polyethylene glycol-biscarbamate dimethacrylate; and the polymerizable monomer is a polyethylene glycol acrylate monomer.

3. The unsaturated zwitterionic polymer according to claim 2, characterized in that: The polyethylene glycol acrylate monomer includes at least one of methoxy polyethylene glycol acrylate, ethylene glycol monomethyl ether acrylate and polyethylene glycol methyl ether methacrylate; The number average molecular weight of the methoxy polyethylene glycol acrylate is 480-10000; the number average molecular weight of the polyethylene glycol methyl ether methacrylate is 300-4000.

4. The unsaturated zwitterionic polymer according to claim 1, characterized in that The unsaturated zwitterionic compound comprises at least one of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, 2-methacryloyloxyethylphosphocholine, and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate; The lithium salt comprises at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium nitrate, lithium difluorophosphate and lithium difluorooxalatoborate; The plasticizer includes at least one of ethylene carbonate, propylene carbonate, tetraethylene glycol dimethyl ether, 1-n-butyl-3-methylimidazolium hexafluorophosphate and 1-allyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide; The initiator includes at least one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-2-methyl-1-phenylpropanone and 1-hydroxycyclohexylphenylketone.

5. An unsaturated zwitterion-based polymer membrane, characterized in that: The invention comprises a base film and a polymer loaded on the base film; the polymer is the unsaturated zwitterionic polymer according to any one of claims 1 to 4.

6. The unsaturated zwitterion-based polymer membrane according to claim 5, characterized in that: The base membrane is a polyethylene membrane, a polypropylene membrane, a cellulose membrane, a glass fiber membrane, a polyvinylidene fluoride membrane or a polyacrylonitrile membrane; the loading amount of the polymer on the unsaturated zwitterionic polymer membrane is 85% to 95%.

7. The method for preparing the unsaturated zwitterion-based polymer membrane according to any one of claims 5 to 6, comprising the following steps: The base film is immersed in a precursor solution for immersion treatment, and the obtained immersed base film is subjected to light irradiation to in-situ polymerize the base film to generate an unsaturated zwitterionic polymer to obtain the unsaturated zwitterionic polymer film; the precursor solution comprises the raw material for preparing the unsaturated zwitterionic polymer according to any one of claims 1 to 4.

8. The preparation method according to claim 7, characterized in that: The immersion treatment time is 10 to 20 minutes; the light source of the light irradiation is ultraviolet light, and the wavelength of the ultraviolet light is 200 to 380 nm; the light irradiation time is 10 to 60 minutes, and the light intensity of the light irradiation is 50 to 200 mW / cm 2 .

9. Use of the unsaturated zwitterion-based polymer according to any one of claims 1 to 4, the unsaturated zwitterion-based polymer film according to any one of claims 5 to 6, or the unsaturated zwitterion-based polymer film obtained by the preparation method according to any one of claims 7 to 8 as a solid electrolyte in a lithium-ion battery.

10. A lithium ion battery comprising a positive electrode, a negative electrode and a solid electrolyte; the solid electrolyte is the unsaturated zwitterion-based polymer according to any one of claims 1 to 4, the unsaturated zwitterion-based polymer film according to any one of claims 5 to 6, or the unsaturated zwitterion-based polymer film obtained by the preparation method according to any one of claims 7 to 8.

Citation Information

Patent Citations

  • Vinyl imidazole polyion liquid-based solid polymer electrolyte membrane for lithium battery and preparation method of vinyl imidazole polyion liquid-based solid polymer electrolyte membrane

    CN116315061A

  • Zwitterionic polymer-based lithium ion battery electrolyte and preparation method thereof

    CN117175000A

  • Novel cross-linker for the preparation of a new family of single ion conduction polymers for electrochemical devices and such polymers

    US20160168086A1

  • Bifunctional ionic liquids for electrolytes

    US20210351436A1

  • Zwitterionic polymer-based aqueous electrolyte having high potential stability window through control of hydration layer and manufacturing method thereof

    WO2024253494A1